2022
DOI: 10.1371/journal.pone.0261806
|View full text |Cite
|
Sign up to set email alerts
|

User experiences of a mobile phone-based health information and surveillance system (mHISS): A case of caregivers of children under-five in rural communities in Ghana

Abstract: Background The rapid advancement of mobile technology has fueled the use of mobile devices for health interventions and for improving healthcare provision in underserved communities. Despite the potential of mHealth being used as a health information and surveillance tool, its scale-up has been challenging and, in most cases, unable to advance beyond the pilot stage of implementation. The purpose of this study was to explore user experiences of a mobile phone-based interactive voice response (IVR) system among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Like our ndings, existing research on mobile health interventions has shown that ease of use, technical assistance, user education, and awareness campaigns contribute to the adoption and usage of digital interventions [34,35,41,42]. This calls for a more user-centric approach to the development and implementation of the add-on(s) in Ghana and other countries considering implementing mobile-phone based technology in the healthcare system.…”
Section: Enhancing the Mrs Through Add-onssupporting
confidence: 65%
See 1 more Smart Citation
“…Like our ndings, existing research on mobile health interventions has shown that ease of use, technical assistance, user education, and awareness campaigns contribute to the adoption and usage of digital interventions [34,35,41,42]. This calls for a more user-centric approach to the development and implementation of the add-on(s) in Ghana and other countries considering implementing mobile-phone based technology in the healthcare system.…”
Section: Enhancing the Mrs Through Add-onssupporting
confidence: 65%
“…Our participants argued that involving key actors like the implementation agencies, policymakers, developers, and potential users and improving infrastructure may improve the relevance and of the add-ons as in recent studies [26, [32][33][34][35]. The identi cation of long-term funding as one of the main factors that could in uence the implementation of the add-ons in this study aligns with existing literature that has highlighted the challenges associated with implementing and maintaining digital health solutions due to inadequate funding [35,36]. This implies that collaboration between governments, international organizations, and the private sector is essential to support the implementation of effective mobile health interventions worldwide.…”
Section: Enhancing the Mrs Through Add-onsmentioning
confidence: 98%
“…IVR can be used as a standalone tool, or can be combined with other tools/methods to augment data collection and dissemination as was done by the International Organization for Migration (IOM) in Cox’s Bazaar, Bangladesh, where participants were screened using an IVR survey to identify those eligible to receive a call back with a specific needs assessment survey [ 23 , 24 , 35 ]. IVR has been shown to be acceptable and useful in qualitative studies and a mobile phone-based IVR health information and surveillance system in Ghana was demonstrated to support user healthcare decision-making and disease awareness [ 36 ]. IVR is being explored as a data collection tool to reach groups that are often missed using conventional techniques with promising initial results [ 37 ].…”
Section: Introductionmentioning
confidence: 99%